2022
DOI: 10.1007/s11121-022-01432-x
|View full text |Cite|
|
Sign up to set email alerts
|

The Strong African American Families Program: Disrupting the Negative Consequences of Racial Discrimination Through Culturally Tailored, Family-Based Prevention

Abstract: Racism continues to be a major source of stress for African Americans and can impair psychological functioning. Adolescents experiencing discrimination may engage in self-soothing, but risky behaviors, which leave them at risk for negative life trajectories. Black pride has been identified as a key factor in explaining the heterogeneity in responses to discrimination. Racial socialization, strategies parents use to promote Black pride and protect youth from discrimination, is an important focus of family-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…For instance, resilience was oftentimes framed as a protective factor influenced by other processes. This observation was noted by Berkel and colleagues (2022) in this manner: “African American parents’ use of racial socialization is a determining factor in nurturing these key elements of resilience (p. 2). Another common framing of resilience consisted of explicitly naming behaviors and practices used as a strategy for coping, however, these coping mechanisms were largely discussed “in spite of” oppressive forces (i.e., systematic racism).…”
Section: Resultsmentioning
confidence: 74%
“…For instance, resilience was oftentimes framed as a protective factor influenced by other processes. This observation was noted by Berkel and colleagues (2022) in this manner: “African American parents’ use of racial socialization is a determining factor in nurturing these key elements of resilience (p. 2). Another common framing of resilience consisted of explicitly naming behaviors and practices used as a strategy for coping, however, these coping mechanisms were largely discussed “in spite of” oppressive forces (i.e., systematic racism).…”
Section: Resultsmentioning
confidence: 74%
“…Despite renewed protections for mental health parity in the Affordable Care Act, a survey in 2017 revealed that a behavioral health care office visit for a child/teen was 10 times more likely to be out-of-network than a primary care visit-twice the disparity seen for adults (Melek et al, 2019). Migrant children/families are at higher risk for a range of mental health concerns and have even more limited access to care (Beier & Fredricks, 2023;Bunn & Betancourt, 2022;Burbage & Walker, 2018).…”
Section: Mental Healthmentioning
confidence: 99%
“…E. Hoagwood et al, 2018). Murry and her colleagues have developed and tested a targeted two-generation, community-centered program ( Strong African American Families [SAAF]) that has shown consistently strong results in promoting the well-being and health behaviors of Black youth living in rural areas (Berkel et al, 2024). More recently, they have adapted elements of this program for delivery in an online platform ( Pathways for African Americans Success [PASS]) that retains efficacy and increases reach to more families (Murry et al, 2019).…”
Section: The Way Forwardmentioning
confidence: 99%
“…PROSAAF was found to increase effective parenting; in a second model, effective parenting moderated the association of racial discrimination with depressive symptoms. Berkel et al 24 examined data from a trial of the SAAF program for early adolescents. They found that SAAF promoted racial pride which, in turn interacted with discrimination and was associated with downstream psychological adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…They found that SAAF promoted racial pride which, in turn interacted with discrimination and was associated with downstream psychological adjustment. Although these 2 studies 23 , 24 with early adolescents suggest the potential for family-centered prevention to moderate the association of discrimination with adverse outcomes, their designs prevent strong causal inferences.…”
Section: Introductionmentioning
confidence: 99%